Association of Severity and Prognosis With Elevated Homocysteine Levels in Patients With Intracerebral Hemorrhage - Wang, Dandan; Wang, Wenjuan; Wang, Anxin; Zhao, Xingquan (Frontiers in Neurology, 2020)
Background: Intracerebral hemorrhage (ICH) has a high mortality and morbidity in the world. Homocysteine (Hcy) has demonstrated as an independent risk factor and could predict the prognosis and recurrence of ischemic stroke. In our study, we aimed to find out the relationship between Hcy levels and the severity and prognosis of patients with ICH. Methods: Patients’ basic characteristics and laboratory examination results, including the concentration of homocysteine were taken at baseline from January 2014 to September 2016, and a one- year follow up, including the modified Rankin Scale and living status were taken for all the patients. Logistic regression and Kaplan-Meier survival method were used to analyze the relationship between different Hcy levels and clinical outcome. Results: A total of 551 patients with acute ICH from 13 hospitals in Beijing were enrolled in our study. 284 (51.5%) of them had a high Hcy. Percentage of male, smoking, drinking and concentrate of hemoglobin A1c and triglyceride levels showed significant difference between different Hcy level groups (all P values < 0.05). In the logistic regression analysis, high Hcy is an independent risk factor for the prevalence of 3- month poor prognosis (odd ratio (95% confidence interval) = 1.601(1.063-2.412), P=0.0242), especially in female subgroup. In the 1- year follow- up period, the high Hcy level patients had a significantly higher rate of fatal incidence compared to normal Hcy level patients (P=0.0023). Conclusions: High Hcy level was independently associated with poorer 3-month prognosis and a lower survival rate within one year in patients with ICH.